Siti Walidah, Gender Equality and Modernist Islamic Women's Movement in Indonesia: A Critical History - Lailatul Huda; Dwi Susanto (Islamica: Jurnal Studi Keislaman, 2023)
This study delves into Siti Walidah’s journey as a gender equality pioneer within the ‘Aisyiyah movement, utilizing four research methods: heuristic research for source collection, source criticism for source validation, interpretation employing sociological and anthropological approaches, and historiography for systematic reporting. Findings reveal that Walidah’s family and marriage to Ahmad Dahlan strongly influenced her commitment to gender equality. Dahlan played a significant role in forming views and experiences that gave birth to ideas and tangible actions in the gender equality movement. Walidah pioneered the gender equality movement by establishing places of education: launching the Sapa Tresna association (1914), ‘Aisyiyah (1917), Internaat (1919), Musholla ‘Aisyiyah (1922) which became tools for building gender equality by providing opportunities and programmes for women to obtain equal educational rights as men. She played a pioneering role in empowering women within ‘Aisyiyah, leading its congresses, and departed from religious values to advocate for gender equality through the ‘Aisyiyah organization formed in 1917, solidifying her legacy as Indonesia’s first gender equality advocate.